Identifying Antecedents and Consequences of Customer Satisfaction in the Full-Service Airline Industry - Margaretha Pink Berlianto (Jurnal Manajemen, 2019)
This study aims to investigate the effect of brand image, perceived value, and loyalty programs on satisfaction and the effect of satisfaction with customer advocacy on Garuda Indonesia airways customers. The population of this study was individuals who had used Garuda Indonesia airways by distributing questionnaires as many as 200 samples. The sampling technique used was purposive sampling. Data analysis using PLS-SEM. The results of this study indicate that brand image, perceived value, and loyalty programs have a positive effect on satisfaction and satisfaction have a positive effect on customer advocacy. This research has succeeded in contributing to the airline industry regarding the importance of increasing band image, perceived value and organizing loyalty programs and also forming customer advocacy.